Nanotechnology Based Therapeutic Approach in Alzheimer’s - Samiullah, Md.; Chauhan, Kajal; Manimekalai, K.; Sherief, S. Hameedullah; Pandya, Maulik K.; Ahmed, Soaib; Bhaskar, Roushan; Prakash, Jay (Journal for Research in Applied Sciences and Biotechnology, 2024)
Alzheimer's disease is a neurodegenerative disorder that ultimately results from the accumulation of beta-amyloid plaques in the brain. The Alzheimer's disease cannot be prevented or cured at this time, and there is no recognised alternative. The medicinal solutions that are currently available can merely slow down its development. However, nanotechnology has demonstrated its applications in the medical field, and it demonstrates a great deal of promise in the treatment of Alzheimer's disease. In particular, it has shown significant promise in the detection of the condition and the development of an alternative technique to cure it. It is necessary for the medication delivery system to have the capability of penetrating and crossing the blood-brain barrier in order to accomplish this need. On the other hand, greater research is necessary in order to discover and overcome these limitations, which have the potential to improve drug absorption while simultaneously reducing toxicity and adverse effects. Certain nanotechnology-based techniques to treating Alzheimer's disease include regenerative medicine, neuroprotection, and stem cell regeneration. These are just few of the emerging approaches. This article's goal is to take a look at nanotechnology from every angle, including its advantages and disadvantages and how it's helping with neurodegenerative disease research and therapy.